The role of clinical pharmacists in improving diabetic care of hospitalized heart patients - Sanaa Mekdad; Leenah Alsayed; Susan Alkhulaif (Diabetes Epidemiology and Management)
Introduction: Globally, diabetes is becoming an increasingly prevalent chronic illness. Managing glucose levels in patients with diabetes presents a significant challenge that requires collaboration with medical specialists. Clinical pharmacists play a crucial role in diabetes management, positively influencing patient outcomes and improving overall quality of care. Objectives: The purpose of this research is to understand how clinical pharmacists at King Fahad Medical City impact the management of hospitalized patients with diabetes and cardiac conditions. Method: A prospective randomized study was conducted at the Cardiac Center of King Fahad Medical City, involving patients admitted between 2019 and 2023. Participants were assigned to one of two groups: one managed by clinical pharmacists (n = 500) and the other receiving standard care without clinical pharmacists (n = 500). Patients were followed up with six months following the clinical pharmacist's intervention, as well as concurrently with data collection, baseline measurements of glycosylated hemoglobin (HbAC), fasting blood glucose (FBG), and the frequency of hypoglycemic episodes. after intervention. Concurrently, included (HbA1c), after intervention. Concurrently, collection included (HbA1c), episodes following the Results: Both groups demonstrated a decrease in HbA1c levels. The intervention group experienced a reduction in HbA1c from 10.2 % to 8.5 % (SD = 2.2, p = 0.04). In contrast, the control group showed a decrease in HbA1c from 9.95 % to 9.05 % (SD = 1.95, p = 0.05). Additionally, fasting blood glucose (FBG) levels in the intervention group decreased by 29 mg/dL, while the decline in the control group was not statistically significant, at 9 mg/dL. The difference in HbA1c levels was statistically significant, as determined by both t-tests. Conclusions: As a member of a multidisciplinary team, a clinical pharmacist can play a crucial role in monitoring diabetes in hospitalized patients with heart conditions. Their interventions can more effectively lower HbA1c levels and fasting blood glucose (FBG) in these patients compared to standard care.